.NET and COM : the complete interoperability guide - Nathan, Adam, 1977- (Sams, 2002)
"The scope of the book is just about everything related to using "unmanaged code" in the .NET Framework. Technologies built on top of COM Interoperability are also covered-Interoperability of Windows Forms Controls and ActiveX controls, Interoperability with COM+, and Interoperability with Distributed COM (DCOM)"--Resource description page.